Meningkatkan Pemahaman Siswa SMA Don Bosco 3 Cikarang Mengenai Internet Sehat, Gamifikasi Dan Pergaulan Lawan Jenis di Era Digital - Rosalina, Rosalina; Sahuri, Genta; Mandala, Rila; Fahmi, Hasanul (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2023)
In today's digital age, high school students have to survive a dynamic and interconnected online environment. Promoting responsible digital citizenship and cultivating pleasant contacts, particularly those with the opposite sex, is critical as kids develop both intellectually and socially. The goal of this activity is to: (1) educate high school students about the responsible and ethical use of the internet, emphasizing the importance of online safety, privacy, and respect for others; (2) encourage students to develop healthy internet usage habits by providing them with the knowledge and tools to navigate the digital world responsibly; and (3) use gamification principles to engage and motivate high school students to adopt responsible online behavior. The activity was held at SMA Don Bosco 3 Cikarang and was attended by students as well as teachers.